Plasma Deposition of Ti-C Based Coating on AISI 420 Steel Using Titanium Cathodic Cage and Graphite Lid - Brenda Jakellinny de Sousa Nolêto; Marcos Cristino de Sousa Brito; Lucas Pereira da Silva; Lauriene Gonçalves da Luz Silva; Renan Matos Monção; Ediones Maciel de Sousa; Cesar Augusto Antônio Junior; Luciana Sgarbi Rossino; Thercio Henrique de Carvalho Costa; Cleânio da Luz Lima; Samuel Filgueiras Rodrigues; Rômulo Ribeiro Magalhães de Sousa (Materials Research)
This work investigates the plasma deposition of Ti-C based coatings on AISI 420 steel using a cathodic cage technique with titanium and graphite components. The study examines two treatment conditions: cathodic potential and floating potential samples, with the objective of evaluating their influence on the coating properties. The results indicate that the cathodic potential treatment results in the formation of thicker coatings with enhanced microhardness, thereby improving wear resistance. Although both treatments demonstrated satisfactory wear resistance, they negatively impacted the corrosion resistance of the steel. X-ray diffraction analysis revealed the formation of TiC, Fe3C, Cr7C3 and Cr23C6 phases in the treated samples, which contribute to the improved microhardness and wear resistance. Wear tests confirmed reduced wear volume in the treated samples. The cathodic potential treatment exhibited greater microhardness and an extensive carburized layer, but the corrosion and wear resistance were similar in both conditions.